2018
DOI: 10.2306/scienceasia1513-1874.2018.44.179
|View full text |Cite
|
Sign up to set email alerts
|

Determination of antioxidant activity of gum arabic: An exudation from two different locations

Abstract: Gum arabic (GA) is the main product of acacia trees. As a raw and commercial samples, GA was extracted with methanol and analysed to measure the antioxidant activity using five methods: 2,2-diphenyl-1-picrylhydrazyl (DPPH), Folin-Ciocalteu indexes (FCI), which indicate total phenolic compounds (TPC), oxygen radical absorbance capacity (ORAC), ferric reducing antioxidant power (FRAP), and cupric reducing antioxidant capacity (CUPRAC). This study used antioxidant assays to detect TPC and selected appropriate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 34 publications
1
27
0
2
Order By: Relevance
“…The increase in the antioxidant activity can also be related to the use of encapsulating material, since gum arabic also has the capacity of reducing free radicals. However, according to Mirghani et al (2018), the antioxidant activity of gum arabic with DPPH was the one with the lowest result. Bernstein and Noreña (2015) reported that the antioxidant activity of red cabbage extract in acidified water was approximately 34.6% and, in dehydrated products, it decreased to values between 14 and 22.5%, highlighting that this decrease was a consequence of high air temperatures at the atomizer outlet, which caused the degradation of compounds responsible for the antioxidant activity.…”
Section: Antioxidant Activity Dpphmentioning
confidence: 96%
“…The increase in the antioxidant activity can also be related to the use of encapsulating material, since gum arabic also has the capacity of reducing free radicals. However, according to Mirghani et al (2018), the antioxidant activity of gum arabic with DPPH was the one with the lowest result. Bernstein and Noreña (2015) reported that the antioxidant activity of red cabbage extract in acidified water was approximately 34.6% and, in dehydrated products, it decreased to values between 14 and 22.5%, highlighting that this decrease was a consequence of high air temperatures at the atomizer outlet, which caused the degradation of compounds responsible for the antioxidant activity.…”
Section: Antioxidant Activity Dpphmentioning
confidence: 96%
“…In this research, antioxidant activity of GAE was better than of G. verrucosa from Pok Tunggal water (IC50= 188.53 ppm) [13], while antioxidant activity of ULE was still relatively low compared by U. lactuca extract [43] that have strong antioxidant activity (IC50= 60.975 ppm). The different result occurs because the antioxidant activity are varied, depends on the species of seaweed [44], location [45] and seasons [14], respectively. Antioxidant compound act as a hydrogen atom donor [46].…”
Section: Resultsmentioning
confidence: 99%
“…In this present research, The IC50 value was slightly higher (72.95 ±0.22 ppm) than Sedjati et al (2018) (69,274 ppm) and lower than Hidayati et al (2017) (99.166 ppm). The different result occurs because the antioxidant activity are varied, depends on the species of seaweed (Parthiban et al, 2014), location (Mirghani et al, 2018) and seasons (Khairy and El-Sheikh, 2015), respectively. The low IC50 value indicates a strong antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%